Disparities in HIV clinic care across Europe: findings from the EuroSIDA clinic survey. Issue 1 (December 2016) - Lazarus, Jeffrey; Laut, Kamilla; Safreed-Harmon, Kelly; Peters, Lars; Johnson, Margaret; Fätkenheuer, Gerd; Khromova, Irina; Vandekerckhove, Linos; Maciejewska, Katarzyna; Radoi, Roxana; Ridolfo, Anna; Mocroft, Amanda
Abstract Background Although advances in HIV medicine have yielded increasingly better treatment outcomes in recent years, HIV-positive people with access to antiretroviral therapy (ART) still face complex health challenges. The EuroSIDA Study Group surveyed its clinics to explore regional differences in clinic services. Methods The EuroSIDA study is a prospective observational cohort study that began enrolling patients in 1994. In early 2014, we conducted a 59-item survey of the 98 then-active EuroSIDA clinics. The survey covered HIV clinical care and other aspects of patient care. The EuroSIDA East Europe study region (Belarus, Estonia, Lithuania, the Russian Federation and Ukraine) was compared to a "non-East Europe" study region comprised of all other EuroSIDA countries. Results A larger proportion of clinics in the East Europe group reported deferring ART in asymptomatic patients until the CD4 cell count dropped below 350 cells/mm3 (75 % versus 25 %, p  = 0.0032). Considerably smaller proportions of East Europe clinics reported that resistance testing was provided before ART initiation (17 % versus 86 %, p  < 0.0001) and that it was provided upon treatment failure (58 % versus 90 %, p  = 0.0040). Only 33 % of East Europe clinics reported providing hepatitis B vaccination, compared to 88 % of other clinics (p  < 0.0001). Only 50 % of East Europe clinics reported having access to direct-acting antivirals for hepatitis C treatment, compared to 89 % of other clinics (p  = 0.0036). There was significantly less tuberculosis/HIV treatment integration in the East Europe group (27 % versus 84 %p  < 0.0001) as well as significantly less screening for cardiovascular disease (58 % versus 90 %, p  = 0.014); tobacco use (50 % versus 93 %, p  < 0.0001); alcohol consumption (50 % versus 93 %, p  < 0.0001); and drug use (58 % versus 87 %, p  = 0.029). Conclusions Study findings demonstrate how specific features of HIV clinics differ across Europe. Significantly more East Europe clinics deferred ART in asymptomatic patients for longer, and significantly fewer East Europe clinics provided resistance testing before initiating ART or upon ART failure. The East Europe group of clinics also differed in regard to hepatitis B vaccination, direct-acting antiviral access, tuberculosis/HIV treatment integration and screening for other health issues. There is a need for further research to guide setting-specific decision-making regarding the optimal array of services at HIV clinics in Europe and worldwide.